2013
DOI: 10.4236/ajps.2013.42041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Farmyard Manure and Inorganic Fertilizer Application on Soil Physico-Chemical Properties and Nutrient Balance in Rain-Fed Lowland Rice Ecosystem

Abstract: A field experiment was conducted to assess the effects of combined application of farm yard manure (FYM) and inorganic NP fertilizers on soil physico-chemical properties and nutrient balance in a rain-fed lowland rice production system in Fogera plain, northwestern Ethiopia. The study was carried out during the main cropping seasons of 2010 and 2011. Twenty-seven treatments comprising a factorial combination of three rates of FYM (0, 7.5, and 15 t·ha ) were tested. The experiments were laid out as a randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
66
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 7 publications
15
66
0
2
Order By: Relevance
“…The application of FYM increased Olsen-P because of its P content, and possibly by increasing retention of P in soil. These results were similar to the results reported by Ayoola and Titilola (2006), Walia et al, (2010), Moharana et al, (2012), Datt et al, (2013), Tadesse et al, (2013).…”
Section: Available Phosphorussupporting
confidence: 82%
See 1 more Smart Citation
“…The application of FYM increased Olsen-P because of its P content, and possibly by increasing retention of P in soil. These results were similar to the results reported by Ayoola and Titilola (2006), Walia et al, (2010), Moharana et al, (2012), Datt et al, (2013), Tadesse et al, (2013).…”
Section: Available Phosphorussupporting
confidence: 82%
“…The bulk density of soil increased with depth 15 to 30 cm, varying from 1.18 to 1.30 g cm -3 in all the treatments. These results are similar to those reported by Walia et al, (2010), Nayak et al, (2012), Datt et al, (2013), Tadesse et al, (2013).…”
Section: Soil Bulk Densitysupporting
confidence: 82%
“…This might be due to favorable soil condition by the application of organic manure which increased activity of microbes and thereby increase in available phosphorus status of soil. Similar findings were observed by Tadesse et al, (2013). It is clear from the data that the available K, S and Zn status in soil after harvest of rice crop varied due to the application of various combination of organic and inorganic source of nutrient.…”
Section: Availability Of N P K S Znsupporting
confidence: 77%
“…Quansah (2010) similarly reported that application of poultry manure in combination with household waste onto the soil significantly increased its moisture retention due to added organic matter into the soil. Liu et al (2013) and Tilahun et al (2013) similarly found that incorporation farm yard manure into soil significantly reduced SBD and yet at the same time significantly increased SMC due to large amounts of organic matter and organic carbon added on the soil.…”
Section: Soil Water Content (Smc) Soil Bulk Density (Sbd) and Crop Wmentioning
confidence: 89%